2015
DOI: 10.1016/j.jacc.2015.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Time to Cost-Effectiveness Following Stroke Reduction Strategies in AF

Abstract: Both NOACs and LAAC with the Watchman device were cost-effective relative to warfarin, but LAAC was also found to be cost-effective and to offer better value relative to NOACs. The results of this analysis should be considered when formulating policy and practice guidelines for stroke prevention in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…11 Interestingly, the economics of LAA occlusion therapy using the Watchman device relative to both warfarin and novel oral anticoagulants (NOACs) has been the subject of several prior economic analyses. [12][13][14] When examining model-based economic analyses of medical care involving chronic disease therapies (such as AF), 2 points are worth keeping in mind. First, before considering any cost data, attention should be directed to the clinical effectiveness story reflected in the model and how that relates to the understanding of effectiveness based on empirical trial data.…”
Section: See Article By Freeman Et Almentioning
confidence: 99%
“…11 Interestingly, the economics of LAA occlusion therapy using the Watchman device relative to both warfarin and novel oral anticoagulants (NOACs) has been the subject of several prior economic analyses. [12][13][14] When examining model-based economic analyses of medical care involving chronic disease therapies (such as AF), 2 points are worth keeping in mind. First, before considering any cost data, attention should be directed to the clinical effectiveness story reflected in the model and how that relates to the understanding of effectiveness based on empirical trial data.…”
Section: See Article By Freeman Et Almentioning
confidence: 99%
“…However, it should be the weaker argument against LAAC. Different studies have demonstrated the cost-effectiveness of the LAAC procedure for NVAF [2,3,15]. What's more, all of them have demonstrated its superiority over the NOACs.…”
Section: Price / Reimbursement Issuesmentioning
confidence: 99%
“…The ICER per QALY gained of LAAC over warfarin has been calculated as low as $3,432 [15]. A very interesting study [3] e) The same group of investigators performed a similar analysis [2] in patients with absolute contraindications to warfarin. The selected comparators for the LAAC were aspirin plus clopidogrel [18] and apixaban [14].…”
Section: Price / Reimbursement Issuesmentioning
confidence: 99%
“…10 In this issue of the Journal, Kim et al 11 report their Korean registry data of LAAC using the Watchman device as well as the Amplatzer Cardiac Plug (St. Jude Medical Inc, MN, USA) implantation. What we learn is the real-world acute success rate of this procedure in Asian patients, and the prevalence of periprocedural safety events, which we have to make as few as possible.…”
Section: Percutaneous Left Atrial Appendage Closure For Non-valvular mentioning
confidence: 99%